An In Vivo Quantitative Comparison of Photoprotection in Arabidopsis Xanthophyll Mutants - Ware, Maxwell A.; Dall’Osto, Luca; Ruban, Alexander V. (Frontiers in Plant Science, 2016)
Contribution of different LHCII antenna carotenoids to protective NPQ (pNPQ) were tested using a range of xanthophyll biosynthesis mutants of Arabidopsis: plants were either devoid of lutein (lut2), violaxanthin (npq2), or synthesized a single xanthophyll species, namely violaxanthin (aba4npq1lut2), zeaxanthin (npq2lut2) or lutein (chy1chy2lut5). A novel pulse amplitude modulated (PAM) fluorescence analysis procedure, that used a gradually increasing actinic light intensity, allowed the efficiency of pNPQ to be tested using the photochemical quenching (qP) parameter measured in the dark (qPd). Furthermore, the yield of photosystem II (ΦPSII) was calculated, and the light intensity which induces photoinhibition in 50% of leaves for each mutant was ascertained. Photoprotective capacities of each xanthophyll were quantified, taking into account chlorophyll a/b ratios and excitation pressure. Here, light tolerance, pNPQ capacity and ΦPSII were highest in wild type plants. Of the carotenoid mutants, lut2 (lutein-deficient) plants had the highest light tolerance, and the joint the highest ΦPSII with violaxanthin only plants. We conclude that all studied mutants possess protective NPQ and a more complete composition of xanthophylls in their natural binding sites is the most important factor governing photoprotection, rather than any one specific xanthophyll, suggesting a strong structural effect of the molecules upon the LHCII antenna organisation and discuss the results significance for future crop development.